Non-cognitive skills and individual earnings: New evidence from PIAAC - Brindusa Anghel; Pau Balart (SERIEs - Journal of the Spanish Economic Association, 2017)
We use the Programme for the International Assessment of Adult Competencies (PIAAC) data to construct several measures of non-cognitive skills and to analyze the relationship between non-cognitive skills and earnings. We construct measures for non-cognitive skills based on previous research in the field, such as self-reports and non-response in the background questionnaire. We also take advantage of the computer based nature of the assessment to explore the effects of other constructs such as skipped questions in the test, average time per question, average time per correct answer and the number of keyboard and mouse movements before answering a question. We find that, even after controlling for PIAAC scores, previously proposed proxies of non-cognitive skills (self-reports and survey non-response) are significantly associated with individual earnings. We also use these measures of non-cognitive skills to propose a correction of the PIAAC scores as a measure of cognitive skills in the earnings equation. By doing so, we observe that the relationship between earnings and PIAAC scores might be partially mediated by non-cognitive skills. However, our results also show that PIAAC test scores remain highly significant and as the main determinant of earnings after the correction.
Keywords: I21; I26; 330; Non-cognitive skills; Earnings; PIAAC data